(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of knowledge on anaphylaxis prevention and treatment of nurses and study some related factors at Ha Dong General Hospital in 2025. Research methods: Cross-sectional descriptive study of 204 nurses in clinical departments from January to July in 2025. Data were collected by questionnaire using a toolkit designed based on the Ministry of Health’s anaphylaxis prevention guidelines. Data were analyzed using SPSS 26.0 software. Results: General knowledge about anaphylaxis reached a high level of 97.5%. Knowledge about prevention (89.7%) and treatment (85.3%) was also high. Some specialized content was still limited: 18.6% did not know how to properly test for drug reactions according to the Ministry of Health’s instructions; 22.1% did not know about the symptoms of severe anaphylaxis; and about 50% of subjects did not know how to dilute adrenaline. Factors related to knowledge include: Nurses trained in anaphylaxis while still in school, trained at the hospital and experience in anaphylaxis management (p < 0.01). Conclusion: It is necessary to strengthen training, coaching and supervision to improve the quality of nursing.